1975
DOI: 10.1029/ja080i025p03549
|View full text |Cite
|
Sign up to set email alerts
|

Protons as the prime contributors to storm time ring current

Abstract: Following a large sudden commencement on June 17, 1972, a large magnetic storm evolved, with a well‐developed main phase and recovery phase. Explorer 45 (S³‐A), with its apogee near 16 hours local time in June, measured the equatorial particle populations and magnetic field throughout this period. By use of data obtained during the symmetric recovery phase it is shown that through a series of self‐consistent calculations, the measured protons, with energies from 1 to 872 keV, can account for almost all of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

1975
1975
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…The updated B is substituted into . Following the calculations of Hoffman and Bracken [1967] and Berko et al [1975], we repeated this procedure three times. Berko et al [1975] showed that the magnetic field calculated with three iterations approached the observed magnetic field.…”
Section: Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The updated B is substituted into . Following the calculations of Hoffman and Bracken [1967] and Berko et al [1975], we repeated this procedure three times. Berko et al [1975] showed that the magnetic field calculated with three iterations approached the observed magnetic field.…”
Section: Simulationmentioning
confidence: 99%
“…Following the calculations of Hoffman and Bracken [1967] and Berko et al [1975], we repeated this procedure three times. Berko et al [1975] showed that the magnetic field calculated with three iterations approached the observed magnetic field. We confirmed that three iterations are sufficient because calculations with four or five iterations reach almost the same result as the three‐iteration calculation.…”
Section: Simulationmentioning
confidence: 99%
“…Until the recent work by Lyons and Evans (1976) and Tinsley (1916), in which they suggest He + as a significant ion, ring current studies have assumed or stated that hydrogen was the dominant ion composing the ring current (Berko et al, 1975; and others before that). However, 0 + ions have been shown to be the dominant ion species under geomagnetic stormtime conditions at low altitudes (Shelley et al, 1972;Sharp pt al., 197ba,b).…”
Section: Backg;•oundmentioning
confidence: 99%
“…The main carriers of the ring current are thought to be ions with energies of a few keV to hundreds of keV [e.g., Frank, 1967a;Smith and Hoffman, 1973;Berko et al, 1975;Williams, 1981;Krimigis et al, 1985;Daglis et al, 1993]. During quiet times, the ring current mainly consists of protons, while during storm times, O + ions detectors on the Explorer 45 spacecraft and assuming that the measurements were for protons only, showed that at L~4, over~80% of the ring current energy density is contained in protons with energies of~20-300 keV during both quiet times and storm times.…”
Section: Introductionmentioning
confidence: 99%